PM Design of IPMSM using Parameterized Finite Element Model - Huijuan Liu; Haijiao Zhang; Jingxiong Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, a parameterized transient finite element model for permanent magnet (PM) dimension analysis and performance simulation of a V-shape interior permanent magnet synchronous motor (IPMSM) with 8 poles is developed. The relationships between induced electromotive force (EMF) and PM dimension, cogging torque and PM dimension are analyzed; the geometries of PM structure are optimized by performing response surface methodology (RSM); a new type of flux-barrier is designed to weaken the flux leakage, and the performances of the sample IPMSM are simulated. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3745